The Financial Drivers of CSR Disclosure: Evidence from Indonesian Coal Mining Companies - Ramadhan, Syahril; Nugroho, Arissetyanto; Darmasyah, Darmansyah (Universitas Jakarta Internasional, 2024)
This study explores the influence of company size, profitability, and leverage on Corporate Social Responsibility (CSR) disclosure among coal mining companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Despite the increasing global emphasis on sustainability reporting, research on CSR disclosure determinants in emerging markets, particularly in coal mining industry, remains limited. This study is examining how financial and organizational factors shape CSR disclosure in a sector that faces intense scrutiny due to its environmental and social footprint. Utilizing stakeholder theory, legitimacy theory, and resource-based theory, the research employs multiple linear regression analysis to investigate these relationships. The findings reveal that company size positively impacts CSR disclosure, indicating that larger firms are more likely to engage in CSR activities to meet stakeholder expectations and maintain legitimacy. However, profitability and leverage do not significantly affect CSR disclosure, suggesting that financial performance and risk levels do not directly dictate CSR practices in the examined companies. These results underscore the importance of contextual factors and strategic resource allocation in understanding CSR disclosure. For policymakers, the findings highlight the need for regulatory measures that encourage all firms, regardless of size or financial standing, to enhance transparency in sustainability reporting. For corporate managers, it suggests that CSR disclosure should not be solely driven by financial performance but rather integrated into long-term stakeholder engagement and risk management strategies. Given the growing expectations for environmental accountability, companies should proactively align their CSR initiatives with regulatory trends and stakeholder demands to enhance legitimacy and competitive advantage.